Roasting treatments affect oil extraction rate, fatty acids, oxidative stability, antioxidant activity, and flavor of walnut oil - Li, Huankang; Han, Jiajia; Zhao, Zhongkai; Tian, Jinhu; Fu, Xizhe; Zhao, Yue; Wei, Changqing; Liu, Wenyu (Frontiers in Nutrition, 2023)
The quality of pressed walnut oil can be improved by moderate roasting treatment. This study compared physicochemical characteristics and antioxidant ability of walnut oils pressed from differently roasted pretreated walnuts, analyzed the correlation among these indicators by using Pearson correlation coefficient and correlation coefficient heatmap, and evaluated the volatile organic substances (VOCs) of walnut oil under optimal pretreatment roasting conditions using headspace-gas chromatography-ion mobility spectrometry (HS-GC-IMS). Roasting treatment at 120 °C for 30 min increased the content of oleic (5.09%), linolenic (5.19%) and palmitic (2.33%) acids in walnut oil. Walnut oil pressed from walnuts roasted at 150 °C for 30 min had the highest content of linolenic acid. After roasting at 120 °C for 20 min, the FRAP and ABTS values of walnut oil were remarkably higher than those of the other samples (p<0.05), while the highest value of DPPH appeared at 120 ℃ for 10 min. Hierarchical cluster analysis (HCA) and principal component analysis (PCA) were able to remarkably distinguish walnut oil produced by different roasting processes. In addition, correlation analysis showed that there was a significant impact among indicators. There were 73 VOCs were identified in the optimum roasted treated walnut oil, consisting of 30 aldehydes, 13 alcohols, 11 ketones, 10 esters, 5 acids, 2 oxygen-containing heterocycles, 1 nitrogen-containing heterocycle and 1 other compound. GC-IMS results showed that aldehydes contributed significantly to the volatile flavor profile of walnut oil, especially (E)-2-heptenal, (E)-2-pentenal and hexenal.